Editorial - Deniz Evcik (Archives of Rheumatology, 2011)
The Year in Review for the Turkish Journal of Rheumatology I want to introduce you to the last issue of 2011 and also provide a list of the most read original articles from the last three issues. These were respectively: 1. Diagnostic Accuracy of the 2002 EULAR Criteria for the Clinical Suspicion of Rheumatoid Arthritis and the Sensitivity of the New 2010 ACR/EULAR.[<r1>] 2. Comparison of the Therapeutic Efficacy of Diclofenac Sodium and Methyl Salicylate Phonophoresis in the Management of Knee Osteoarthritis.[<r2>] 3. Turkish League Against Rheumatism National Recommendations for the Management of Ankylosing Spondylitis.[<r3>] 4. Let me also give a very special thanks to the authors of these articles. Also, we noticed an increase in genetical studies, and five articles on this topic were published in different issues this year. Three of these genetical studies were related to vitamin D polymorphisms.[<r4>-<r6>] One of them was on the subject of the human glucocorticoid receptor gene (NR3C1) Bcl-1 CG polymorphism in rheumatoid arthritis (RA) patients and the other was regarding Glu298Asp, -786T>C, and Intron 4 a/b Polymorphisms of the Endothelial Nitric Oxide Synthase Gene in Behçet’s Disease.[<r7>,<r8>] We think these studies enriched the journal immensely and hope new genetical studies will also be published in upcoming issues. It is now a pleasure to introduce you to the national recommendations for the management of rheumatoid arthritis which were done under the umbrella of the Turkish League Against Rheumatism (TLAR) study group. Also, in order to be useful for every physician dealing with rheumatology in Turkey, the Turkish translation of the article will be posted on our website (www.trasd.org.tr). I want to thank all our contributers and Bayçınar Medical Publishing for their hard work in making this journal successful. Happy new year and best wishes for the year 2012. With my best regards, Prof. Dr. Deniz Evcik Editor